(untitled) (Journal of Business Management and Accounting, 2011)
In contrast to the large-scale multinational projects, medical tourism sector in Kerala mainly constitutes indigenous health management practices coupled with local tourism industry. The government and bureaucracy project medical tourism as an engine of economic growth. It is considered as an excellent source of foreign exchange and employment generation to revive the local economy. As it mainly involves indigenous methods and techniques of health care management, further development and sustainability of this sector fully depends on highly committed, skilled and qualifi ed manpower. However, no detailed studies regarding the potential problems faced by the human resource capital in this sector are available. This paper is an attempt to analyze the various challenges associated with the work-life balance (WLB) of the employees working in the indigenous health care management practices linked to the medical tourism industry of Kerala, India. Data for the study were collected from 157 individuals, working in the medical tourism sector spanning around 24 organizations. The results indicated the positive and negative associations of the various challenges with the WLB of the employees.